The Effect of Otic Melanocyte Destruction on Auditory and Vestibular Function: a Study on Vitiligo Patients - Parvane Mahdi; Amin Amali; Masoumeh Ruzbahani; Akram Pourbakht; Asadollah Mahdavi (Acta Medica Iranica, 2016)
The hallmark of vitiligo is the disappearance of melanocytes from the skin. As a result, of melanocytes presence in the auditory and vestibular apparatus, the involvement of these systems in vitiligo which targets the melanocytes of the whole body is possible; suggesting that vitiligo is a systemic disease rather than a purely cutaneous problem. A total of 21 patients with vitiligo were enrolled in this study. A group of 20 healthy subjects served as a control group. Pure tone audiometry (PTA), auditory brainstem responses (ABR) and vestibular evoked myogenic potentials (VEMP) were carried out in all participants. High frequency sensory neural hearing loss was seen in 8 (38.09%) patients. ABR analysis revealed 10 (47.61%) had an abnormal increase in latency of wave III, and 6 (28.57%) had an abnormal prolongation of IPL I-III, however, regarding our VEMP findings, there were no recorded responses on left ear of 1 (4.76%) patient and latency of p13 was prolonged in 5(23.80%) patients. There was no correlation between ages, duration of disease, and any of the recorded parameters (P>0.05). In the present survey, we highlighted the auditory and vestibular involvement in vitiligo patients.